Isolated Pd Sites as Selective Catalysts for Electrochemical and Direct Hydrogen Peroxide Synthesis - Ledendecker, Marc; Pizzutilo, Enrico; Malta, Grazia; Fortunato, Guilherme; Mayrhofer, Karl; Hutchings, Graham J.; Freakley, Simon J. (ACS Catalysis, 2020)
Palladium nanoparticles have been studied extensively as catalysts for the direct synthesis of hydrogen peroxide, where selectivity remains a key challenge. Alloying Pd with other metals and using acid and halide promoters are commonly employed to increase H2O2 selectivity; however, the sites that can selectively produce H2O2 have not been identified and the role of these additives remains unclear. Here, we report the synthesis of atomically dispersed PdClx/C as a model catalyst for H2O2 production without the presence of extended Pd surfaces. We show that these isolated cationic Pd sites can form H2O2 with significantly higher selectivity than metallic Pd nanoparticles in both the reaction of H-2 and O-2 and the electrochemical oxygen reduction reaction. These results demonstrate that catalysts containing high populations of isolated Pd sites are selective catalysts for this two-electron reduction reaction and that the performance of materials in the direct synthesis reaction and electrocatalytic oxygen reduction reaction has many similarities.
CRIS-Team WoS Importer:2020-06-09